CIPPO Evaluation at School Providing Inclusive Education at Elementary School - Imam Yuwono (Journal of ICSAR, 2017)
This evaluation study aims to determine the effectiveness of the implementation of inclusive Elementary School Gadang 2 in Banjarmasin. This evaluation study used a CIPP model and data collection techniques used questionnaires, interviews, observation and study documentation. Analysis of data used qualitative descriptive technique developed by Glickman’s with quadrant type. The results of this evaluation study gave a conclusion that implementation of inclusive education program in Gadang 2 Banjarmasin less effective. Some things are not in accordance with the evaluation criteria, namely: the stated goals were not in accordance with the realities today, the recruitment of students with special needs have not done well, the school was not equipped with adequate infrastructure and financing remains low besides social attitudes as a component of outcome was not in accordance with the evaluation criteria